KETAHANAN PANGAN DAN PENINGKATAN PENDAPATAN PETANI MELALUI TUMPANG SARI KANGKUNG DAN KELOR DI KELURAHAN BONTORAMBA KECAMATAN SOMBAOPU KABUPATEN GOWA - Muh. Ardiansyah; Abdul Halil; Asriyanti Syarif; Andi Rahayu Anwar (Universitas Muhammadiyah Makassar, 2023)
AbstractThe water Spinach and morinaga intercropping system is an agricultural product in the context of increasing farmer income and efforts to fulfill family food. The research was conducted in the Bontoramba sub-district, Sombaopu District, Gowa Regency by sampling in a saturated sample with a total of 36 farmers doing intercropping farming of moringa and kale. The sampled farmers were given questions using a questionnaire guide and conducted group discussion forums (FGD). Data were analyzed using income analysis, and farmers' perceptions of food security (income, available food sources, as well as the level of farmers' knowledge were analyzed in percentage form and strengthened by presentation in verbal form. Income from water spinach farming was Rp.1,896. 178.22/Ha in one growing season, while Moringa farming provides an income of IDR 669,954.91/Ha. Kale farming income is greater than Moringa because the amount of production is greater than Moringa.Meanwhile, farmers' perceptions of food security in terms of income with the system intercropping, they agree by 83.33% that income provides an alternative for farmers to fulfill food in order to support food security Farmers' perceptions of food security in terms of fulfilling food needs, they agree by 100% that intercropping can meet food needs (vegetables) for farmers and lutes price, and nutritional needs are met. Farmers' perceptions of food security in terms of knowledge agree by 77.78% that there are benefits from these two plants being intercropped as vegetables, although there is still a lack of knowledge about the other benefits of kale and moringa plants, as well as more detailed knowledge of the reasons for these two plants being intercroppedKeywords: food security, income, intercropping, kale, moringa